Adolescent sexuality and life skills education in Nigeria: to what extent have out-of-School adolescents been reached? (2014)
The introduction of school-based adolescent sexuality and life skills education in Nigeria’s formal education sector raises the misgiving that out-of-school youths who constitute more than half of the youth population might be neglected. This study investigated the extent to which out-of-school adolescents have been reached with sexuality education in Nigeria. The study took place in the six geopolitical zones and the Federal Capital Territory Abuja, and involved out-of-school adolescents, Non-Governmental Organizations, and community leaders. The qualitative research approaches were employed. Most of the youths had been exposed to sexuality education through seminars, trainings and workshops organized by different organizations. However, states in the south were better served than those in the north. Sexually Transmitted Infections including HIV/AIDS prevention accounted for more than 40% of the content of sexuality and life skills education received by out-of-school adolescents. The programmes have impacted positively on adolescents’ disposition and relationship with the opposite sex, knowledge and skill building.